Some aspects of urban micro-climate in Kuala Lumpur West Malaysia - Sham Sani, (Universiti Kebangsaan Malaysia, 1972)
This report present results of observations of temperature and humidity on two relatively cloudy days in Kuala Lumpur. The results show that first, the city-core is generally warmer and drier than the countryside and large open areas; second, the highest daily temperatures are recorded in the city-core; third, the minimum temperatures everywhere are reached round about 0500-0600 hours and fourth, the physiological temperatures follow closely the patterns of the air temperatures and reach their highest values in the city streets.